Age-specific Mortality Rates in Nepal by Using Lee-Carter Model - Paudel, Sudhan; Phulara, Keshab Raj (Nepal Journal of Mathematical Sciences, 2025)
This study analyzes and forecasts age-specific mortality rates in Nepal using the Lee-Carter model. Using a dummy variable to account for the impact of the 2015 earthquake, this research presents a methodological adaptation of the Lee-Carter Model. The model is estimated through singular value decomposition and regression, and the mortality rates are forecasted to 2030. The results highlight gender specific mortality differences and an overall decline in mortality rates over time. While the study is limited by availability of only five years of data, the findings still provide valuable insights into epalese mortality trends. Datasets of larger time frames and region-specific data would further strengthen the model’s predictive capabilities and provide quality insights.